Oncogenic Fusions in Gliomas: An Institutional Experience - Polivka, Jiri; Svajdler, Marian; Priban, Vladimir; Mracek, Jan; Kasik, Petr; Martinek, Petr; Ptakova, Nikola; Sharif Bagheri, Mahyar; Shetti, Dattatrya; Pesta, Martin; Potuznik, Pavel; Topolcan, Ondrej (Anticancer research, 2022)
BACKGROUND/AIM: Gliomas are primary malignancies of the central nervous system (CNS). High-grade gliomas are associated with poor prognosis and modest survival rates despite intensive multimodal treatment strategies. Targeting gene fusions is an emerging therapeutic approach for gliomas that allows application of personalized medicine principles. The aim of this study was to identify detectable fusion oncogenes that could serve as predictors of currently available or newly developed targeted therapeutics in cross-sectional samples from glioma patients using next-generation sequencing (NGS). PATIENTS AND METHODS: A total of 637 patients with glial and glioneuronal tumours of the CNS who underwent tumour resection between 2017 and 2020 were enrolled. Detection of fusion transcripts in FFPE tumour tissue was performed by a TruSight Tumour 170 assay and two FusionPlex kits, Solid Tumour and Comprehensive Thyroid and Lung. RESULTS: Oncogene fusions were identified in 33 patients. The most common fusion was the KIAA1549-BRAF fusion, detected in 13 patients, followed by FGFR fusions (FGFR1-TACC1, FGFR2-CTNNA3, FGFR3-TACC3, FGFR3-CKAP5, FGFR3-AMBRA1), identified in 10 patients. Other oncogene fusions were also infrequently diagnosed, including MET fusions (SRPK2-MET and PTPRZ1-MET) in 2 patients, C11orf95-RELA fusions in 2 patients, EGFR-SEPT14 fusion in 2 patients, and individual cases of SRGAP3-BRAF, RAF1-TRIM2, EWSR1-PALGL1 and TERT-ALK fusions. CONCLUSION: The introduction of NGS techniques provides additional information about tumour molecular alterations that can aid the multimodal management of glioma patients. Patients with gliomas positive for particular targetable gene fusions may benefit from experimental therapeutics, enhancing their quality of life and prolonging survival rates.
Keywords: Humans; Quality of Life; targeted therapy; onkogeny; protein-serin-threoninkinasy; adaptorové proteiny signální transdukční; Receptor-Like Protein Tyrosine Phosphatases, Class 5; lidé; Adaptor Proteins, Signal Transducing; Oncogenes; gene fusion; kvalita života; Oncogene Fusion; Protein Serine-Threonine Kinases; Microtubule-Associated Proteins; proteiny asociované s mikrotubuly; gliom; onkogenní fúze; next-generation sequencing; Cross-Sectional Studies; průřezové studie; molecular genetics; Glioma; tyrosinfosfatasy receptorového typu, třída 5